Convergence of Known Distributions to Limiting Normal or Non-normal Distributions: An Elementary Ratio Technique. Issue 3 (3rd July 2017) - Bagui, Subhash; Mehra, K. L.
ABSTRACT: This article presents an elementary informal technique for deriving the convergence of known distributions to limiting normal or non-normal distributions. The presentation should be of interest to teachers and students of first year graduate level courses in probability and statistics.